Long-Term Effect of Nutrient Management on Soil Microbial Properties and Nitrogen Fixation in a Vertisol under Soybean– Wheat Cropping Sequence - Anay Rawat, R.K. Thakur1; Neeta Mahawar, Jalendra Bairwa, B.S. Dwivedi* (Journal of the Indian Society of Soil Science, 2021)
The present experiment was conducted during 2018-19 under the ongoing All India Coordinated Research Project on Long-term Fertilizer Experiment with soybean-wheat cropping sequence since 1972 at the Research Farm of Department of Soil Science and Agricultural Chemistry, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India. The microbial properties and nitrogen (N2) fixation of soil under different nutrient combinations were studied in a 46-year old long-term fertilizer experiment in a Vertisol. The experiment was conducted in a randomized block design comprising of 10 treatments viz., T1: 50% NPK, T2: 100% NPK, T3: 150% NPK, T4: 100% NPK + Hand weeding (100% NPK+HW), T5: 100% NPK + zinc (100% NPK + Zn), T6: 100% NP, T7: 100% N, T8: 100% NPK+ 5 t FYM ha-1 (100% NPK+FYM), T9: 100% NPK(–S) and T10: Control, each treatment being replicated four times in a randomized block design. Soil samples from all the treatments were collected from 0–15 cm depth and microbial properties and N2 fixation of soil were estimated. Significant increase in soil organic carbon, total N and available N were recorded with 100% NPK+FYM. Similarly, the maximum number of nodules and their biomass were also recorded in 100% NPK+FYM treatment at 30, 45 and 60 days after sowing. The bacteria, fungi and actinomycetes population counts in soil were 39.1×107, 42.7×104 and 39.1×105 cfu g-1 soil, respectively with the integrated application of inorganic fertilizer and organic manure (100% NPK+FYM) over control (11.7×107, 18.5×104 and 13.6×105 cfu g-1 soil, respectively). Further, the conjoint use of balance dose of fertilizers with FYM was also significantly superior in terms of soil microbial biomass carbon and microbial biomass N over other treatments even after 46 years of experimentation. The grain and straw yield of soybean and their N uptake were also significantly increased with graded dose of fertilizers and maximum yield and N uptake were noted in 100% NPK+FYM treatments over control plot.